Maternal and fetal arrhythmia as a sign of hemodynamic deterioration: a case report - I.V. Lakhno; I.M. Sykal; S.M. Korovai; V.M. Korotych; A.E. Tkachov (Український журнал Здоров'я жінки)
The co-existing maternal (MA) and fetal arrythmia (FA) are associated with maternal goiter disease, chorioamnionitis, or Ballantyne’s syndrome.